PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2008 PADA PT. INSERA SENA - Kusuma, Niko Permana; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to find out the actual impact of the implementation of quality management system ISO 9001:2008 and its advantage which is gained by PT. Insera Sena. The research object in this research is focused on the implementation of the management system ISO 9001:2008 and it has been carried out by using qualitative descriptive which analyzes some elements of quality audit which has been implemented by the research object which compares with the guideline of quality. The result of the research shows that PT. Insera Sena which builds quality management system based on ISO 9001:2008 has been prepared and examined in order to make it conforms with all activities within the company. In order to ensure the effectiveness on the implementation of quality management system ISO 9001:2008 which has been run is properly controlled and to make continuous improvement, coordination among employees in each department within the company is required to be carried out.Keywords: management system, ISO 9001:2008, manufacturing company